2012
DOI: 10.1002/app.38683
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and performance evaluations of electrospun poly(ε‐caprolactone), poly(lactic acid), and their hybrid (50/50) nanofibrous mats containing thymol as an herbal drug for effective wound healing

Abstract: The use of herbal drugs as biocompatible and nontoxic drugs without special side effects in wound dressings are highly favored compared to that of chemical and synthetic drugs. In this study, the properties and performance of electrospun poly(ε‐caprolactone) (PCL), poly(lactic acid) (PLA), and their 50/50 hybrid nanofibrous mats containing the herbal drug thymol (1.2% v/v) as wound dressings were investigated. The optimized solution concentrations of PCL (12% w/v) and PLA (3% w/v) in chloroform/dimethylformami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
111
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(117 citation statements)
references
References 33 publications
6
111
0
Order By: Relevance
“…The fraction of solventaccessible PD increases with increasing PD content because of (a) geometrical consideration similar to the release of lysozyme at increasing lysozyme loading (Puhl et al, 2014) and (b) increased swelling of the matrix (Fig. 4B), resulting in improved water penetration into the polymer matrix (Dordunoo et al, 1997;Karami et al, 2013). However, at a higher PD content of 50% (PCL/ PD50) relative release was reduced to 80.5 AE 5.7% compared to almost complete release observed with PCL/PD20.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The fraction of solventaccessible PD increases with increasing PD content because of (a) geometrical consideration similar to the release of lysozyme at increasing lysozyme loading (Puhl et al, 2014) and (b) increased swelling of the matrix (Fig. 4B), resulting in improved water penetration into the polymer matrix (Dordunoo et al, 1997;Karami et al, 2013). However, at a higher PD content of 50% (PCL/ PD50) relative release was reduced to 80.5 AE 5.7% compared to almost complete release observed with PCL/PD20.…”
Section: Discussionmentioning
confidence: 95%
“…6A). To explain these observations a release model based on (a) PD-induced desorption of lysozyme from the polymer matrix and (b) increased matrix swelling with increasing PD content and thus a diffusion controlled mechanism is proposed (Karami et al, 2013;Yang et al, 2001). Recently, Srikar et al (2008) reported a model describing the release of hydrophilic drugs from electrospun, slowly degrading polymer matrices.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, the percentage of polar compounds of oil can favor the entrapment of aqueous phase into de microcapsules during the coacervation process and consequently slows down its diffusion [119]. Nevertheless, the release rate profiles of thymol from the PCL (poly(e-caprolactone)), PLA, and 50/50 hybrid nanofibrous samples, performed by Karami et al [128] point out a bi-phasic release profiles. The Fickian diffusion was the dominant mechanism of thymol release from the polymeric matrices.…”
Section: Diffusion Characteristics Of Poly(lactic Acid) Microcapsulesmentioning
confidence: 99%
“…The effect of antifungal contents on gas permeability of the films was more pronounced when increasing the concentration of thymol to 20 %. This could be because thymol acted as a plasticizer and rearranged the polymer chains layers [16] subsequently lower the degree of crystallinity and increased the free volume in the polymer matrix.…”
Section: Smae 2016mentioning
confidence: 99%